The productivity effects of privatization in Ukraine: Estimates from comprehensive manufacturing firm panel data, 1989 -2005 - J. David Brown; John S. Earle (W.E. Upjohn Institute for Employment Research, 2007)
This paper estimates the effect of domestic and foreign privatization on multifactor productivity (MFP) using long panel data for nearly the universe of initially state-owned manufacturing firms in Ukraine. The longitudinal dimension of the data is used to measure and control for pre-privatization selection bias and to estimate long-run impacts. The data imply steadily increasing MFP as a result of domestic privatization, reaching about 25 percent relative to state-owned firms after six years. Until recently, Ukraine has had relatively few cases of privatization to foreign investors, and estimates of the MFP impact are more sensitive to controls for selection bias, but the results suggest foreign privatization produces a productivity advantage of about 40 percent in 2004-2005.
Keywords: D24; G34; L33; P31; 330; productivity; privatization; selection bias; foreign ownership; Ukraine; Privatisierung; Produktivität; Verarbeitendes Gewerbe; Direktinvestition; Ukraine